Observation and origin of organochlorine compounds and polycyclic aromatic hydrocarbons in the free troposphere over central Europe - Lammel, Gerhard; Klánová, Jana; Kohoutek, Jirí; Prokes, Roman; Ries, Ludwig; Stohl, Andreas (Environmental pollution (Barking, Essex, 2009)
On Zugspitze (2670 m a.s.l.), Alps, higher concentrations were observed during a winter than during a summer measurement campaign of PAHs, chlorobenzenes (43.6 vs. 2.0 pg m(-3)) and DDTs (3.7 vs. 1.2 pg m(-3)), while hexachlorocyclohexanes and PCBs were found at similar levels. The PCB, HCH and DDT levels are among the lowest ever reported from outside the Arctic. Mostly lower levels were found in samples collected in summer than in winter despite a significant boundary layer air influence, but no such influence on samples collected during the winter campaign. Boundary layer influence was quantified by Lagrangian particle dispersion model retroplume analyses. Photochemical lifetimes corresponding to k(OH) < 1.5 x 10(-12) cm(3) molec(-1) s(-1) are found for p,p'-DDT, k(OH) < 0.75 x 10(-12) cm(3) molec(-1) s(-1) for p,p'-DDE and k(OH) < 1.0 x 10(-12) cm(3) molec(-1) s(-1) for p,p'-DDD.
Keywords: Atmosphere; Europe; Seasons; Evropa; látky znečišťující vzduch; Air Pollutants; chlorované uhlovodíky; polycyklické aromatické uhlovodíky; Hydrocarbons, Chlorinated; roční období; atmosféra; Polycyclic Aromatic Hydrocarbons; Environmental Monitoring; monitorování životního prostředí